Sistem Pendukung Keputusan Rekrutmen Karyawan Store Associate - Triana, Helza; Purnama, Beni (Jurnal Manajemen Sistem Informasi, 2023)
Employee recruitment is the activity of selecting and determining a number of applicants who have qualified knowledge and skills and get new, qualified employees. Gramedia Jambi is a retail store that provides various types of books, satationary, office supplies, sport equipment, magazines and tabloids. In the new employee recruitment system, Gramedia Jambi bookstore must pay attention to the existing criteria in the company so that a score is abtained that is objective, accurate and in accordance with the application’s abilities. Less effective time because recruitment is done manually and the difficulty of eliminating subjective factor from HRD. As for the design and implementation of a decision support system for the requitment of new employees by applying the Profile Matching method. The Profile Matching method os a decision-making process by entering ideal values and knowing the apllicant’s abilities because the calculation uses a weighting system. This design aims to assist HRD in recruiting quality employees and in accordance with company criteria. The criteria used are Experience, Knowledge, Appearance, Analyzing Products, Mastering Social Media, and Written Test. The final results of this study overcome problems in employee recruitment at Gramedia Jambi.